Exploring Parents' Attempt to Conduct Home Literacy Practices for Young Learners - Shafa Nurafifah (Universitas Widyatama, 2022)
In Indonesia, it is quite hard to find a study that raised the topic of home literacy even though the topic is very important to discuss. This research will provide an overview of how parents in Indonesia carry out home literacy practices with their children. Thus, this research aimed to explore the types of home literacy practices by Indonesian parents. The researcher collected the data through an interview via Zoom meeting as a method of this research. The data were transcribed and codified under the theory of Burgees, Hect, and Lonigan (2002). For analyzing the data, the researcher uses a thematic analysis. From the findings, it can be known that the mother played a big role in the sustainability of home literacy. While the father’s role in supporting and teaching the Quran or reciting Surah. There are four roles in conducting home literacy as performed by the parents who had the same level of education and from middle and upper economic background. These are the limiting environment, the literacy interface, the active home literacy environment, and the passive home literacy environment.